ANALYSIS OF NUMBER FORM OF NOUNS IN ENGLISH AND UZBEK LANGUAGE - Axmatova Madina,; Muhammadiyev Aziz Shavkatovich, (Лучшие интеллектуальные исследования, 2024)
In this article you can read about differences between making plural nouns in Uzbek and English nouns. Additionally, how can we make plural forms in two languages, their differences and suffices for making for plural nouns.